The poetics of Mirzhakip Dulatovich's artistic image - Gazizov, Г. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2025)
In substantiating the image of historical figures in a work of fiction, every writer, poet-writer gets fully acquainted with the life of this person, historical data, and literature of that period. In Kazakh literature, the image of heroes who showed heroism during the war and the creation of the Kazakh Khanate, the image of great personalities built during the development of the country and educational events of the twentieth century, is illustrated in works of art. The article analyzes in detail the image of the activist Alash, a prominent representative of the national liberation movement, poet and master of leadership Mirzhakip Dulatovich in fiction. The reflection of the existence and social activity of a historical personality in fiction is differentiated on the basis of the works of different writers. In particular, the analysis of the image of Mirzhakyp in the works of such poets and writers as A. Tanirbergenovich, A. Naimanbaevich, M. Zhumabaev, S. Seifullin, M. Titakovich, B. Mailin, T. Jurtbai, J. Abdirash, S. Turgunbekuly and E. Toleubai will be carried out. The distorted images of the Soviet era and realistic and positive assessments of the independence period are relatively considered. In addition, the article says: "Wake up, Kazakh!" profoundly reveals the influence of the slogan on national consciousness, the fate of the prison, the image of a victim of political repression, and the spiritual image in poetry and drama. Through the artistic image of the figure, the national history, the idea of independence and the desire for historical justice are revealed.